Upaya Peningkatan Minat dan Prestasi Belajar Sejarah Melalui Metode Mind Mapping pada Siswa Kelas X IPA 1 SMA Negeri 1 Sewon - Marharjono Marharjono (Ideguru: Jurnal Karya Ilmiah Guru, 2019)
This study aims to, 1) increase interest in learning history through the method of learning Mind Mapping in class X science 1 students of SMA Negeri 1 Sewon 2016/2017 school year. 2) improve the history of learning achievement through the Mind Mapping learning method in class X science 1 students of SMA Negeri 1 Sewon 2016/2017 academic year. This research was conducted in class X Science 1 of SMA Negeri 1 Sewon in 2016/2017 school year. The study used the Classroom Action Research (CAR) approach, with two cycles. Data collection techniques in this study used observation, questionnaires, and historical learning outcomes tests. The instruments used in this study were observation guidelines, questionnaires, and historical learning achievement tests. The data analysis technique used in this research is comparative descriptive by comparing pre-action data, cycle I and cycle II. The results showed that 1) the application of the Mind Mapping method was able to increase learning interest. Student interest in learning categories is good and very good, in pre-cycle as many as 13 students (54.17%), in the first cycle increased from 17 students (70.83%) at the first meeting, to 19 students (79.17%) at the meeting second. In cycle II, it increased from 21 students (87.50%) at the first meeting, to 22 students (91.67%) at the second meeting. 2) The application of the Mind Mapping method can improve historical learning achievement in students of class X Science 1 of SMA Negeri 1 Sewon in the 2016/2017 school year. Historical learning achievement increased from the classical average of 69.38 and mastery learning by 15 students (62.50%) in the pre-cycle, increased to an average of 79.25 and mastery learning by 19 students (79.17%) in the first cycle, and an average of 86.67 and completeness of learning as many as 22 students (91.67%) in the second cycle.